THEORIES OF NURSING: REFLECTION AS CRITIC CONSTRUCTION INSTRUMENT OF THE ELABORATED KNOWLEDGE - Fátima Luna Pinheiro Landim; Mirna Albuquerque Frota; Lorita Marlena Freitag Pagliuca (Universidade Federal do Paraná, 2001)
The meanings of the theories for the nursing profession raise in the theorists an alert posture and committed with the scientific intention that is directed to a self-understanding, feedback and presuppositions analysis and the theoretical-philosophical bases of statement of the nursing as body of knowledge to serve the formation, exercise and professional updating for the mankind benefit. Thus, the reflection in nursing, goes by the concern with its 'scientificity' and the conscious elaboration of this reflection. Criticalreflexive study that aimed the following objectives: answer the Theory of the Diversity and Universality of the Care is simple; to verify the complexity degree checked by the theory to an empiric research in nursing. In the treatment of the data, it was considered the analysis model and basic route of subjects suggested by Chinn and Kramer (1995) to proceed with the "critical reflection of the nursing theories". The conclusion is that the high number of concepts, subconcepts, presupposed and developed terms, as well as the a lot of existent interrelations among them, give the Theory of the Diversity and Universality of the Care high Cultural complexity degree. In other hand, an empiric research was verified inside of the nursing sciences, that uses the theory without, however, let contaminate for its complexity.